Strengthening MSMEs’ Competitiveness through Digital Marketing Strategies: A Community Service Approach - Setia Hidayah; Muhammad Zulfikar; Rosnani Siregar (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2025)
Digital development has significantly influenced business practices, particularly for Micro, Small, and Medium Enterprises (MSMEs), which are required to adapt to technological changes in order to remain competitive. However, many MSMEs still rely on conventional marketing methods and have limited understanding of digital marketing and digital financial management. This community service program aims to strengthen MSMEs’ competitiveness through the implementation of digital marketing strategies that support market expansion and improve business sustainability. The program was conducted using a qualitative descriptive approach through a series of community service activities, including field observations, interviews, seminars, and mentoring sessions for MSME actors. The focus of the activities was to introduce and assist MSMEs in utilizing digital marketing platforms, particularly social media such as Instagram, TikTok, and Facebook, as well as online marketplaces, to promote products more effectively. In addition, MSME participants were introduced to basic digital financial applications to support more structured and transparent financial recording. The results of the community service activities indicate positive changes among MSME participants, including increased awareness of the importance of digital marketing, improved product branding, broader market reach beyond local areas, and better financial management practices compared to previous manual recording methods. The adoption of digital marketing strategies enabled MSMEs to communicate product information more efficiently and build consumer trust through online presence. This community service program demonstrates that digital marketing assistance combined with practical mentoring can enhance MSMEs’ competitiveness and contribute to improving community economic welfare. Continuous support and consistency from MSME actors are essential to ensure the sustainability of digital transformation initiatives.